The Role of Victimology in the Protection of Victims of Traffic Accidents - Aswani (Yayasan Mentari Madani, 2024)
Every activity contains the danger of accidents. Anyone can have an accident anywhere, including on the highway. The chance of an accident on the road increases due to the high level of community mobility. The study of victim issues, including those arising from traffic accidents, is known as victimology. The Road Traffic and Transportation Law Number 22 of 2009 regulates traffic accidents in Indonesia. Families of victims who died in car accidents act as witnesses to help police identify victims and reconstruct incidents. Without eliminating the charges against the defendant, the victim's family also participates in the peace process, namely determining the amount of compensation that must be given as accountability